Photographic and Radiometric Observations of the HAYABUSA Re-Entry - Borovicka, J.; Abe, S.; Shrbený, L.; Spurney, P.; Bland, Phil (Nihon Tenmon Gakkai, 2011)
We analyzed photographic observations of the re-entry of the HAYABUSA spacecraft and capsule over Southern Australia on 2010 June 13, 13:52 UT. Radiometric measurements of the brightness of the associated fireball were obtained as well. We derived the trajectories and velocities of the spacecraft, its four fragments, and the capsule. The capsule trajectory was within a few hundred meters of the trajectory predicted by JAXA prior to re-entry. The spacecraft trajectory was about 1 km higher than the capsule trajectory. Two major fragments separated from the spacecraft at a height of about 62 km with a mutual lateral velocity of 250 m s −1 . The maximum absolute magnitude of the fireball of − 12.6 was reached at a height of 67 km. The dynamic pressures acting on the spacecraft at the fragmentation points were only 1–50 kPa. No spacecraft fragment was seen to survive below a height of 47 km. The integral luminous efficiency of the event was 1.3%. As expected, the capsule had a very low luminous efficiency and very low ablation coefficient. The ablation coefficients and masses of the major spacecraft fragments are discussed.